Bankruptcy and the Concept of Hiwalah (Debt Transfer) in Islamic Economic Law - Khofifah Magfirah; Annisa Fuziyah; Nasrullah Bin Sapa; Darmawati H (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the concepts of bankruptcy (al-Ifl?s) and ?iw?lah from the perspective of Islamic economic law. Bankruptcy has become an important issue in modern economic activities when an individual or institution is unable to fulfill its financial obligations, while hiwalah is an instrument in fiqh muamalah that can serve as a solution for debt transfer. The research employs a normative-juridical approach by analyzing evidences from the Qur’an, Hadith, as well as the views of classical and contemporary scholars. The findings show that Islam regulates bankruptcy based on principles of justice and protection for weaker parties without causing injustice to creditors. Meanwhile, huwalah is a sharia-compliant instrument that can be used to lawfully transfer debt obligations under Islamic law while also reducing risk in financial transactions. The implications of this study affirm that the concepts of bankruptcy and hiwalah in Islamic law are not merely classical doctrines but have strong relevance within the modern Islamic economic legal system, including Islamic banking and financial institutions.